Coping and posttraumatic growth: a longitudinal comparison of two alternative views - Kunz, Simon; Joseph, Stephen; Geyh, Szilvia; Peter, Claudio (American Psychological Association, 2017)
Purpose: The current study aimed to examine two possible explanations for why higher levels of posttraumatic growth (PTG) were repeatedly found to be predicted by both approach - and avoidance - oriented coping, focusing on individuals recently diagnosed with a spinal cord injury (SCI). First, negative changes (posttraumatic depreciation, PTD) may moderate the association between PTG and the two types of coping indicating that PTG reflects avoidance of PTD for some individuals, but a constructive view on posttraumatic life changes for others. Second, it may be that a flexible use of different types of coping strategies (coping flexibility) enables the experience of PTG. Method: A sample consisting of 122 patients admitted to one of the four national SCI rehabilitation centers was examined in a longitudinal study. Hierarchical multiple regression analyses were conducted to test the two competing explanations. Results: Both approach - (β = .30, p = .001) and avoidance - oriented coping (β = .23, p = .011) measured three months after SCI diagnosis predicted higher PTG levels at discharge from clinical rehabilitation. PTD did not moderate the relationship between approach - (β = .03, p = .743) and avoidance – oriented coping (β = - .04, p = .656) and PTG. However, coping flexibility (β = .23, p= .012) predicted higher PTG levels. Conclusion: These results suggest that a flexible use of different types of coping strategies potentially according to situational demands may explain findings that PTG was predicted by both approach-and avoidance-oriented coping.